2015
DOI: 10.1111/wrr.12310
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa uses T3SS to inhibit diabetic wound healing

Abstract: Diabetic foot ulcers are responsible for more hospitalizations than any other complication of diabetes. Bacterial infection is recognized as an important factor associated with impaired healing in diabetic ulcers. Pseudomonas aeruginosa is the most frequently detected Gram-negative pathogen in diabetic ulcers. P. aeruginosa infection has been shown to impair healing in diabetic wounds in a manner that correlates with its ability to form biofilm. While the majority of infections in diabetic ulcers are biofilm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 39 publications
4
72
0
Order By: Relevance
“…Our data demonstrated that the wounds of db/db mice infected with P. aeruginosa exhibited reduced vascularity compared with the wounds of control animals; significantly fewer CD31+ vessels were found in the P. aeruginosa ‐infected wound beds at days 5 and 9 post‐wound injury (Figures F and G). These results confirm that P. aeruginosa impairs wound healing in diabetic mellitus, which is consistent with previous reports (Watters et al, ; Goldufsky et al, ).…”
Section: Resultssupporting
confidence: 93%
“…Our data demonstrated that the wounds of db/db mice infected with P. aeruginosa exhibited reduced vascularity compared with the wounds of control animals; significantly fewer CD31+ vessels were found in the P. aeruginosa ‐infected wound beds at days 5 and 9 post‐wound injury (Figures F and G). These results confirm that P. aeruginosa impairs wound healing in diabetic mellitus, which is consistent with previous reports (Watters et al, ; Goldufsky et al, ).…”
Section: Resultssupporting
confidence: 93%
“…The bacterial species chosen to induce a muscle surgical infection was P. aeruginosa, which is the most prevalent Gram-negative pathogen in all wounds, and it represents 25 % of surgical wound infections (Giacometti et al, 2000;Greif et al, 2000). In line with the importance of P. aeruginosa infection in SSI, we and others have demonstrated that P. aeruginosa uses a variety of virulence mechanisms to inhibit wound healing both in vivo and in vitro in order to propagate its favourite niche 'the wound' (Garrity-Ryan et al, 2004;Shafikhani & Engel, 2006;Zhao et al, 2010;Goldufsky et al, 2015b;Wood et al, 2015a, b). The strain of P. aeruginosa used in this study was PA103, which we and others have described previously (Shafikhani & Engel, 2006;Wood et al, 2013;Goldufsky et al, 2015a, b).…”
Section: Surgical Infection Modelmentioning
confidence: 89%
“…Haematoxylin and eosin (H&E) histological analysis was performed as described (Wood et al, 2014;Goldufsky et al, 2015b). Briefly, at 24 h after surgery and P. aeruginosa or saline muscle injection, rats were euthanized, and the biceps femoris muscle was removed as described (Kroin et al, 2015).…”
mentioning
confidence: 99%
“…On the morning of surgery and bacterial injection, cells were concentrated by centrifugation (1800g) in culture media. Bacterial titers were determined as colony-forming units (CFU) by serial dilution and plating, as previously described, [9][10][11] to provide a 2 Â 10 9 CFU/mL concentration for rats and a 1 Â 10 9 CFU/mL concentration for mice (based initially on optical density and confirmed by serial dilution and plating).…”
Section: S Aureus Cultures For Injectionmentioning
confidence: 99%
“…[9][10][11]13,14 Briefly, the processed samples underwent 10fold serial dilution in PBS to produce 10 −1 to 10 −5 dilutions in 200-μL volume within 96-well microplates, plus an undiluted sample 10 0 . Ten-microliter aliquots of the solutions (10 −5 -10 0 ) were spot plated in duplicate on tryptic soy agar plates and incubated for 24 hours at 37°C.…”
Section: Colony-forming Unit Countingmentioning
confidence: 99%